Comparação de sistemas de avaliação de dietas para bovinos no modelo de produção intensiva de carne. II - Creep feeding - De Brito, Rodolfo Marques [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; Da Cruz, Geraldo Maria [UNESP]; De Alencar, Maurício Mello [UNESP]; Barbosa, Pedro Franklin [UNESP]; Barbosa, Rogério Taveira [UNESP] (My University, 2002)
Twenty-nine suckling Canchim calves averaged 107 kg of body weight and 55 days of age were fed with supplement during the wet season, in order to evaluate the performance provided by nutritional adjustments recommended by different systems of evaluation of diets. Supplements were composed of grounded corn grain, cottonseed meal and soybean meal, in agreement with the recommendations of the Metabolizable Protein System (MP); Cornell Net Carbohydrate and Protein System (CNCPS); and Intestine Digestible Protein System (PDI), for the highest possible body weight gain, according to indications of each adjustment system. The daily body weight gain obtained did not differ among treatments CNCPS, MP and PDI, with mean of 1.0 kg/head for each treatment studied. The body weight differences at weaning, in relation to a control group without supplementation were estimated, so that the creep-feeding would provide monthly net profit of 0, 0.6, 1.2, and 6%, and values of 15.5, 27.1, 17.1, and 15.9 were observed for the CNCPS; 27.9, 17.6, 16.4, and 28.7 for the MP; 18.1, 20.4, 35.6, and 22.5 kg body weight/head for the PDI system. It was concluded that the evaluated supplements provided results compatible with the estimated animal performance.
Comparison of diet evaluation systems for cattle in an intensive beef production model. II - Creep-feeding
Keywords: Brachiaria brizantha; Calves; Feed conversion; Performance